PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN KAFE MOM MILK SEMARANG - Mohammad Rafi; Agung Budiatmo (Universitas Diponegoro, 2018)
The goals of this research are to determine the effect of product quality, service quality and price on purchasing decisions at the consumer cafe Mom Milk Semarang. Type of research using explanatory research with data collection methods by interviews and data collection tools using questionnaires with a sample of 100 respondents consumers Mom Milk Semarang using methods of purposive sampling and Accidental Sampling. The analysis technique used validity test, reliability test, cross tabulation test, simple linear regression, multiple linear regression, t test, and F test with SPSS 25.0. From result of research indicate that product quality influence to purchase decision equal to 31,5%, service quality influence to purchasing decision equal to 33,9% and price influence to purchase decision equal to 42,7%, while simultan product quality, service quality and price effect on purchasing decision equal to 47,5%. It means the better the quality of the product, service quality and price then the higher purchase decision at the cafe Mom Milk Semarang. Price variable to purchase decision variable has bigger effect than product quality and service quality. Based on the results of the study, the researcher suggested that Mom Milk Cafe performs improvements and controls on the manufacture of food or beverages in order to obtain consistent accuracy and evaluate employees, increase employees at certain times to maximize service to consumers, and add facilities that are incomplete in order to consumer convenience.